Multifunctional regulation of VAMP3 in exocytic and endocytic pathways of RBL-2H3 cells - Mishima, Satomi; Sakamoto, Marin; Kioka, Hikaru; Nagata, Yuka; Suzuki, Ryo (Frontiers in Immunology, 2022)
Mast cells (MCs) are inflammatory cells involved in allergic reactions. Crosslinking of the high-affinity receptor for IgE (FcϵRI) with multivalent antigens (Ags) induces secretory responses to release various inflammatory mediators. These responses are largely mediated by soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs). Vesicle-associated membrane protein 3 (VAMP3) is a vesicular-SNARE that interacts with targeted SNARE counterparts, driving the fusion of MC secretory granules with the membrane and affecting subsequent assembly of the plasma membrane. However, the role of VAMP3 in FcϵRI-mediated MC function remains unclear. In this study, we comprehensively examined the role of VAMP3 and the molecular mechanisms underlying VAMP3-mediated MC function upon FcϵRI activation. VAMP3 shRNA transduction considerably decreased VAMP3 expression compared with non-target shRNA-transduced (NT) cells. VAMP3 knockdown (KD) cells were sensitized with an anti-DNP IgE antibody and subsequently stimulated with Ag. The VAMP3 KD cells showed decreased degranulation response upon Ag stimulation. Next, we observed intracellular granule formation using CD63-GFP fluorescence. The VAMP3 KD cells were considerably impaired in their capacity to increase the size of granules when compared to NT cells, suggesting that VAMP3 mediates granule fusion and therefore promotes granule exocytosis in MCs. Analysis of FcϵRI-mediated activation of signaling events (FcϵRI, Lyn, Syk, and intracellular Ca2+ response) revealed that signaling molecule activation was enhanced in VAMP3 KD cells. We also found that FcϵRI expression on the cell surface decreased considerably in VAMP3 KD cells, although the amount of total protein did not vary. VAMP3 KD cells also showed dysregulation of plasma membrane homeostasis, such as endocytosis and lipid raft formation. The difference in the plasma membrane environment in VAMP3 KD cells might affect FcϵRI membrane dynamics and the subsequent signalosome formation. Furthermore, IgE/Ag-mediated secretion of TNF-α and IL-6 is oppositely regulated in the absence of VAMP3, which appears to be attributed to both the activation of FcϵRI and defects in VAMP3-mediated membrane fusion. Taken together, these results suggest that enhanced FcϵRI-mediated signal transduction in VAMP3 KD cells occurs due to the disruption of plasma membrane homeostasis. Hence, a multifunctional regulation of VAMP3 is involved in complex secretory responses in MCs.